The Severe Deficiency of the Somatotrope GH-Releasing Hormone/Growth Hormone/Insulin-Like Growth Factor 1 Axis of Ghrh−/− Mice Is Associated With an Important Splenic Atrophy and Relative B Lymphopenia - Bodart, Gwennaelle; Farhat, Khalil; Renard-Charlet, Chantal; Becker, Guillaume; Plenevaux, Alain; Salvatori, Roberto; Geenen, Vincent; Martens, Henri (Frontiers in Endocrinology, 2018)
A debate is still open about the precise control exerted by the somatotrope GHRH/GH/IGF1 axis on the immune system. The objective of this study was to directly address this question through the use of Ghrh-/- mice that exhibit a severe deficiency of their somatotrope axis. After control backcross studies and normalization for the reduced global weight of transgenic mice, no difference in weight and cellularity of the thymus was observed in Ghrh-/- mice when compared to C57BL/6 wild-type (WT) control mice. Similarly, no significant change was observed in frequency and number of thymic T cell subsets. In the periphery, Ghrh-/- mice exhibited an increase in T cell proportion associated with a higher frequency of sjTREC and naïve T cells. However, all Ghrh-/- mice displayed an absolute and relative splenic atrophy, in parallel with a decrease in B cell percentage. GH supplementation of transgenic mice for 6 weeks induced a significant increase in their global as well as absolute and relative splenic weight. Interestingly, the classical thymus involution following dexamethasone administration was shown to recover in wild-type mice more quickly than in mutant mice. Altogether, these data show that the severe somatotrope deficiency of Ghrh-/- mice essentially impacts the spleen and B compartment of the adaptive immune system, while it only marginally affects thymic function and T cell development.